2018
DOI: 10.1038/s41598-018-31031-2
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome C oxidase Inhibition and Cold Plasma-derived Oxidants Synergize in Melanoma Cell Death Induction

Abstract: Despite striking advances in the treatment of metastasized melanoma, the disease is often still fatal. Attention is therefore paid towards combinational regimens. Oxidants endogenously produced in mitochondria are currently targeted in pre-clinical and clinical studies. Cytotoxic synergism of mitochondrial cytochrome c oxidase (CcO) inhibition in conjunction with addition of exogenous oxidants in 2D and 3D melanoma cell culture models were examined. Murine (B16) and human SK-MEL-28 melanoma cells exposed to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 57 publications
4
28
0
Order By: Relevance
“…[ 3 ] The evidence in the field of medical gas plasma research points to the importance of ROS in mediating plasma‐induced tumor cell death. [ 8 ] The current concept is that these plasma‐derived ROS generate secondary ROS and oxidation products that accumulate inside tumor cells, leading to mitochondrial damage [ 24 ] and pro‐apoptotic signaling. [ 25 ] Exposure of tumor cells to plasma‐derived ROS is accompanied by changes in the release of chemokines and cytokines, [ 26 ] several immunomodulatory receptors, [ 27 ] and upregulation of markers of the immunogenic cancer cell death (ICD) [ 28 ] and cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] The evidence in the field of medical gas plasma research points to the importance of ROS in mediating plasma‐induced tumor cell death. [ 8 ] The current concept is that these plasma‐derived ROS generate secondary ROS and oxidation products that accumulate inside tumor cells, leading to mitochondrial damage [ 24 ] and pro‐apoptotic signaling. [ 25 ] Exposure of tumor cells to plasma‐derived ROS is accompanied by changes in the release of chemokines and cytokines, [ 26 ] several immunomodulatory receptors, [ 27 ] and upregulation of markers of the immunogenic cancer cell death (ICD) [ 28 ] and cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is an important second messenger that is generated by CAP which triggers the release of growth factors during the wound healing process and has been shown to increase keratinocyte viability and migration in wound models [46]. Previous studies have revealed an increase in H 2 O 2 in response to increasing CAP treatments [47]. Intracellular ROS levels also increase in keratinocytes after plasma treat-ment [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…First discovered as a new tool for disinfection and wound healing [12][13][14], plasma also demonstrates cytotoxicity towards cancer cells [15][16][17]. A range of cellular responses have been found, including apoptosis, growth inhibition, cell cycle arrest, as well as cytoskeletal and mitochondrial damage [18][19][20]. The exact mechanism of plasma-induced apoptosis seems to be cell line dependent, varying from Table 1.…”
Section: Introductionmentioning
confidence: 99%